ETHANOL PRODUCTION FROM CASSAVA STARCH USING THE PROCESS STRATEGY SIMULTANEOUS SACCHARIFICATION-FERMENTATION - Hader I. CASTAÑO P. (Universidad de Antioquia, 2009)
The world trend on fuel management, in special biofuels like ethanol, have gone to explorer new methodologies of process to optimize its production by this reason in this research is about simultaneous sacarification fermentation process and evaluate initial concentration of reducing sugar, and enzyme dosing of Spirizyme fuel® are evaluated on productivity and final concentration of ethanol, under SSF (Simultaneous Saccharification and Fermentation) process, from the product of the licuefaction process of cassava starch as substrate. The SSF process is evaluated against SHF (Independent Saccharification and Fermentation) process as control. Only the factor, initial concentration of substrate presents effect over ethanol productivity. The kinetic of SSF process, in opposite to the SHF process, presents time diminution of the global process around 47 y 33% to substrate levels of 150 and 200 g/l respectively. The productivity values are most at a 33% to 150 g/l of reducing sugar, and they keep constant to 200 g/l reducing sugar. The glucose in SSF strategy, at the time it is producing, it is transformed to ethanol, does not allowing to reach superior concentration to 100 g/l of reducing sugar, this implicates there is not substrate inhibition. The ethanol concentration doesn’t affect the enzymatic process of sacharification. The SSF process demonstrates his technical viability on the ethanol production, to reduce time an energy requirements on the ethanol production from cassava flour.